(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Big data analytics is the name given to the process of examining enormous amount of data so the beneath lying patterns can be uncovered. There can be certain correlations that will be revealed during that process and useful information can be easily derived and subsequently used to make absolutely accurate and consistent decisions. Entrepreneurship essence is based on the successful decisions so this analytics revolutionizes the complete process and this systematic approach provides edge over the rivals. This approach makes use of advanced analytic techniques against very large and diverse data sets to deduce the information that is required immediately. Surveys and analysis over time has shown increased profits in the enterprises all over the world. Profits and performance has shown synergic rise. Research on effective use and implementation of information and communication technologies for development suggests that big data technology can make important contributions in international development of the enterprise.